2017
DOI: 10.1007/s13205-017-0993-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and validation of QTLs for cold tolerance at seedling stage in rice from an indica cultivar Habiganj Boro VI (Hbj.BVI)

Abstract: Yellowing, stunting, and seedling death associated with cold stress is a common problem in many Asian countries for winter rice cultivation. Improvement of cultivars through marker-assisted selection of QTLs for cold tolerance at seedling stage from locally adapted germplasm/cultivar is the most effective and sustainable strategy to resolve this problem. A study was undertaken to map QTLs from 151 progenies of a cross between a cold susceptible variety, BR1 and a locally adapted traditional cultivar, Hbj.BVI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Positive and significant associations were also noticed for cold tolerance scoring with root length and cold stress tolerance index Cruz and Milach (2013) [5] , chlorophyll content with seedling height and shoot length Farzin et al (2013) [8] , shoot length with seedling height Siddi et al (2020) [20] . Negative and significant associations were in contrast observed for cold tolerance scale with chlorophyll content ~ 190 ~ Biswas et al (2017) [3] , chlorophyll content with cold stress tolerance index Kim et al (2009) [14] , root length with shoot length. A perusal of these results indicated the need for balanced selection while effecting simultaneous improvement for these traits.…”
Section: Resultsmentioning
confidence: 99%
“…Positive and significant associations were also noticed for cold tolerance scoring with root length and cold stress tolerance index Cruz and Milach (2013) [5] , chlorophyll content with seedling height and shoot length Farzin et al (2013) [8] , shoot length with seedling height Siddi et al (2020) [20] . Negative and significant associations were in contrast observed for cold tolerance scale with chlorophyll content ~ 190 ~ Biswas et al (2017) [3] , chlorophyll content with cold stress tolerance index Kim et al (2009) [14] , root length with shoot length. A perusal of these results indicated the need for balanced selection while effecting simultaneous improvement for these traits.…”
Section: Resultsmentioning
confidence: 99%
“…At 3-leaf stage (approximately 12 -15 days after seeding), the plastic trays were placed in the cold water tank pre-set at 13°C. Sensitivity to cold stress was recorded using an arbitrary leaf discoloration (LD) scores (1 to 9) as described in Biswas et al (2017). LD scores were recorded at seven days after cold treatment or when the susceptible check variety (BR1) died.…”
Section: Evaluation Of Cold Tolerance At the Seedling Stagementioning
confidence: 99%
“…Similarly, QTLs were reported in the F 2 population derived from a cross between a back cross inbred line ( japonica × indica ) and a japonica cultivar Z550 ( Wang et al, 2018 ). Various studies reported QTLs for yield traits in rice using primary mapping populations like F 2:3 ( Sabouri et al, 2009 ; Zhang et al, 2010 ; Kim et al, 2014 ; Tian et al, 2015 ; Biswas et al, 2017 ; Kumar et al, 2019 ) and F 2:4 ( Rabiei et al, 2015 ; Verma et al, 2017 ; Jeon et al, 2018 ; Kumar et al, 2019 ). Crossing of two wild-derived back cross inbred lines generate hybrid lines which can closely resemble the parental lines ( Wang et al, 2018 ) with combination of improved traits.…”
Section: Introductionmentioning
confidence: 99%